Qualitative Evaluation of Fluoride Ions in Different Sodium Fluoride Tablet Formulations Used for Children - F. Mazhari; M. Hassanzadeh-Khayyat; A. Makarem; H. Oraphaii (Wolters Kluwer Medknow Publications, 2007)
Introduction: Use of fluoride tablet is one of the several ways of fluoridation in children. The purpose of this study was to evaluate the systemic absorption of fluoride from a generic sodium fluoride tablet, in comparison with a commercial one.Methods and Materials: This was a double-blind, cross over study. Following ingestion of 1 mg of fluoride in a generic or commercial form, urine samples were collected from 27 healthy boys aged 8-10 years old over a 24-hour period. The urine samples were analyzed by potentiometeric method using fluoride ion selective electrode.Results: Under the identical conditions, the mean 24-hour urinary fluoride excretion rate of the subjects before taking any generic and commercial fluoride tablets were 15.87±4.68 and 17.51±6.40 g/hr, respectively. The average rates of 24-hour urinary fluoride excretion of the subjects were 25.74±6.75 and 28.21±9.23 g/hr after the ingestion of generic and commercial fluoride tables, respectively. The mean cumulative amounts of fluoride ion excreted in 24-hour urine collection were 28% and 22% of the administered doses of commercial and generic fluoride tablets, respectively.Discussion: Results indicated that the systemic absorption of the fluoride ion released from the generic tablet is not significantly different from the commercial one. Therefore, it can be suggestedthat the tested generic tablets is bioequivalent to the commercial ones.